2021
DOI: 10.3390/jmse9121405
|View full text |Cite
|
Sign up to set email alerts
|

Type and Distribution of Microplastics in Beach Sediment along the Coast of the Eastern Gulf of Thailand

Abstract: In the oceans and coasts, plastic waste poses a global threat to biodiversity. This study examined the types and distribution of microplastics in beach sediment along the coast of the eastern Gulf of Thailand in March 2018 (northeast monsoon = dry season) and July 2018 (southwest monsoon = rainy season). Microplastic samples were collected from six stations including Koh Khramyai Beach (Chonburi Province), Koh Mannai Beach (Rayong Province), Chao Lao Beach (Chanthaburi Province, 3 stations), and Ploy Dang Beac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Elsewhere, 54-506 items/kg were found in the Lake of China (Yuan et al, 2019), while another study at the same lake found 244 ± 121 items/kg (Tang et al, 2022). In Thailand, a study on a beach found 0-33 items/kg (Jualaong et al, 2021) and another study on mangrove sediment found 106-180 items/kg (Pradit et al, 2022).…”
Section: Abundance and Occurrence Of Microplastics In Sedimentmentioning
confidence: 98%
“…Elsewhere, 54-506 items/kg were found in the Lake of China (Yuan et al, 2019), while another study at the same lake found 244 ± 121 items/kg (Tang et al, 2022). In Thailand, a study on a beach found 0-33 items/kg (Jualaong et al, 2021) and another study on mangrove sediment found 106-180 items/kg (Pradit et al, 2022).…”
Section: Abundance and Occurrence Of Microplastics In Sedimentmentioning
confidence: 98%
“…It is noted that PE, PP, and PET were found in every sampling month (Table 2). Several broad classes of plastics are used in packaging such as PE, PP, and PET, while PET and nylons are also heavily used in fishing gear applications [44,45]. Rayon fiber is commonly used to produce artificial silk and other textiles [2,12].…”
Section: Polymer Typesmentioning
confidence: 99%
“…The highest microplastic densities were usually associated with coastlines and physical processes in the ocean (Lie et al 2018). Diffusion of microplastics on the coast was strongly related to tides, which was caused by the accumulation of microplastics along the highest tide line, especially at high tide (Jualaong et al 2021). Most of the microplastic present in sediments was carried from other places and arrived at the depositional site by tides, waves, and currents.…”
Section: Microplastic Distribution Vs Coastal Slopementioning
confidence: 99%